Analysis of operational issues in hydrothermal liquefaction and supercritical water gasification processes: a review - Ghavami, Niloufar (2021)
Biomass is often referred to as a carbon–neutral energy source, and it has a role in reducing fossil fuel depletion. In addition, biomass can be converted efficiently into various forms of biofuels. The biomass conversion processes involve several thermochemical, biochemical, and hydrothermal methods for biomass treatment integration. The most common conversion routes to produce biofuels include pyrolysis and gasification processes. On the other hand, supercritical water gasification (SCWG) and hydrothermal liquefaction (HTL) are best suitable for converting biomass and waste with high moisture content. Despite promising efficiencies, SCWG and HTL processes introduce operational issues as obstacles to the industrialization of these technologies. The issues include process safety aspects due to operation conditions, plugging due to solid deposition, corrosion, pumpability of feedstock, catalyst sintering and deactivation, and high production costs. The methods to address these issues include various reactor configurations to avoid plugging and optimizing process conditions to minimize other issues. However, there are only a few studies investigating the operational issues as the main scope, and reviews are seldomly available in this regard. Therefore, further research is required to address operational problems. This study reviews the main operational problems in SCWG and HTL. The objective of this study is to enhance the industrialization of these processes by investigating the operational issues and the potential solutions, i.e., contributing to the elimination of the obstacles. A comprehensive study on the operational issues provides a holistic overview of the biomass conversion technologies and biorefinery concepts to promote the industrialization of SCWG and HTL.